Rural Women's Role in Decision Making Related to Agricultural and Livestock Activities in Jaipur District - Yadav, Seema; Sharma, NK; Sharma, KC; Yadav, Krishna (Indian Journal of Extension Education, 2020)
The study was conducted in two panchayat samities (Dudu and Jalsu) selected randomly from Jaipur districtÂ of Rajasthan. From the selected panchayat samities five villages from each panchayat samiti were selected by using simple random sampling and finally 120 respondents were selected. The data were collected with personal interview schedule. The finding of the study revealed that majority (73.33%) of rural women hadÂ medium participation in decision making agricultural activities. The aspects wise role of rural women in decision making related to agricultural activities, they had near to equally participation in livestock related decisionÂ and farm related decision and statement wise role of rural women in decision making related to agricultural activities, they played important role in â€œManagement of labourâ€ in farm related decision and in livestockÂ related decision they played important role in â€œRetaining milk and other milk products for family consumptionâ€™. There was no significant difference between the rural women of Dudu and Jalsu panchayat samities withÂ respect to their role in decision making related to agricultural and livestock activities.